Traffic Analysis Zone Based Urban Activity Study with Aggregate Mobile Network Data - Chen, Xiqun; Yang, Xinmiao; Shi, Qixin (2009 International Conference on Management and Service Science, 2009)
This paper explores aggregate mobile network data that is real-time and dynamic to reveal urban activities. The principle, method and algorithm of dividing traffic analysis zones (TAZ) and mobile network zones are discussed, a mathematical model of assigning call volume data from mobile network zones to TAZ is established and the corresponding programming process is introduced. Xiangfan is taken as a case study to indicate similarity of mobile phone traffic intensity and person travel survey when the approach is applied. This relativity is of significance to explore and reveal the spatiotemporal pattern of urban activities. Additionally, mobile phone data overcomes disadvantages of the lag, high cost and limitation in quantity of person travel survey. Generally, mobile network data has the features that are refreshing fast, easy to collect, widely used and available in mobile services.